Ireland’s Imperial Connections, 1775–1947
XV, 323 p. 4 illus. in color.
Keywords: This edited collection explores the complexities of Irish involvement in empire. Despite complaining regularly of treatment as a colony by England, Ireland nevertheless played a significant part in Britain’s imperialism, from its formative period in the late eighteenth century through to the decolonizing years of the early twentieth century. Framed by two key events of world history, the American Revolution and Indian Independence, this book examines Irish involvement in empire in several interlinked sections: through issues of migration and inhabitation; through literary and historical representations of empire; through Irish support for imperialism and involvement with resistance movements abroad; and through Irish participation in the extensive and intricate networks of empire. Informed by recent historiographical and theoretical perspectives, and including several detailed archival investigations, this volume offers an interdisciplinary and evolving view of a burgeoning fieldof research and will be of interest to scholars of Irish studies, imperial and postcolonial studies, history and literature.